The Malay Islamic Heritage of Palembang: From the Sultanate to the Present Day - Indah Dwi Cahyani; Hafizo; M.Mawardi; Riyanti; Maryamah (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study examines the development of Malay Islamic heritage in Palembang from the era of the Sultanate to the modern period. As an old city that experienced cultural acculturation between local, Malay, and Islamic traditions, Palembang holds a strong historical legacy in the development of Islam, particularly since the establishment of the Palembang Darussalam Sultanate in the 17th century. The aim of this study is to analyze the intention and transformation of Islamic and Malay cultural values in the lives of Palembang's people. The method used is historical, with a qualitative approach to trace both primary and secondary sources. The results of the study indicate that the legacy of the Palembang Sultanate is still visible in architecture, traditions, and social practices. The Great Mosque of Palembang and the Bala Putra Dewa Museum serve as physical evidence preserving the Malay Islamic identity. However, globalization and cultural regeneration pose challenges to its preservation. In conclusion, although the Malay Islamic heritage in Palembang still exists, more effective preservation strategies are needed to ensure that cultural and religious values remain sustainable amidst changing times.